E-LKPD with a STEM Approach to Enhance Creative Thinking Skills in Science Content on Light and Its Properties among Fifth-Grade Elementary School Students - Putri, Luh Putu Candra Noviana; Astawan, I Gede; Tristiantari, Ni Ketut Desia (Jurnal Pedagogi dan Pembelajaran, 2025)
This research is motivated by the limited availability of e-Worksheets (E-LKPD) as learning media that are suitable for students' needs, as well as the low creative thinking skills of fifth-grade students. The purpose of this study is to determine the design, validity, practicality, and effectiveness of E-LKPD with a STEM approach. This research uses the ADDIE development model with data collection methods using questionnaires and tests with questionnaire sheets and essay tests. The data analysis method in this study is qualitative and quantitative descriptive analysis, meanwhile the effectiveness of the E-LKPD was measured using a one-group pre-test post-test design involving 28 students. The results of the study showed that: (1) the design of E-LKPD with a STEM approach with science content and its properties to improve the creative thinking skills of fifth-grade students; (2) the validation results obtained scores of 95% from material experts and 98.75% from media experts with very valid qualifications; (3) the practicality of E-LKPD based on the results of individual trials was 99.16% and small group trials were 94.16%, both of which are categorized as very practical; and (4) the results of the effectiveness test using the dependent sample t-test showed a significance value (2-tailed) of 0.000 (p less than 0.05), which means there is a significant difference between the pre-test and post-test scores after using the E-LKPD. Therefore, E-LKPD with a STEM approach is effective in improving the creative thinking skills of fifth-grade students.